Enantiomer separation through membrane-based approaches: A review - Hairul Nazirah, Abdul Halim; Mohamed Zulkali, Mohamed Daud, Prof. Madya Dr.; Zulfakar, Mokhtar; Akmal Hadi, Ma'Radzi (Universiti Teknologi MARA (UiTM), 2011)
International Conference on Science and Technology (ICSTIE 2008), Applications in Industry and Education (2008) organized by Universiti Teknologi MARA (UiTM), 12th - 13th December 2008 at Penang, Malaysia.